Influence of Filler Materials on Wettability and Mechanical Properties of Basalt/E-Glass Woven Fabric–Reinforced Composites for Microfluidics - Ayyappa Atmakuri; Lalitnarayan Kolli; Arvydas Palevicius; Sigita Urbaite; Giedrius Janusas (Micromachines, 2022)
This paper presents the development of novel hybrid composites in the presence of filler particles and manufactured using a proposed new fabrication technique. The hybrid composites were fabricated using a basalt and E-glass woven fabric–reinforced epoxy resin matrix combined with graphite powder nanoparticles. Six sets of samples were fabricated using the vacuum-assisted free lamination compression molding technique. After the fabrication, wettability, mechanical properties (tensile, flexural and impact properties) and moisture properties were evaluated. Surface morphology and chemical composition of the composite samples were examined using a scanning electron microscope (SEM) and spectroscopy. The obtained results showed that the use of filler materials in hybrid composites improves the properties of hybrid composites. Basalt/E-glass hybrid composites with 10% graphite material exhibited superior mechanical properties over the other composites, with high-quality, improved adhesion and surface morphology. Thus, novel composites with the combination of exceptional properties may be integrated in the design of flexible electronics and microfluidics devices as a structural layer of the system. High flexibility and good surface tension of the designed composites makes them attractive for using the thermal imprint technique for microfluidics channel design.